Treatment of bauxite residue dust pollution by improving structural stability via application of synthetic and natural polymers - Ding, X.; XU Guang, G.; Zhou Wei, W.; Biswas, Wahidul; Guo Xing-Yun, X. (2019)
The residue drying area (RDA) is the major source of fugitive red sand (RS) dust emissions in the bauxite mining industry and causes serious environmental and safety detriments. Polymer stabilizer (PS) is one of the promising non-traditional stabilizers to mitigate such issues. This research investigated the unconfined compressive strength (UCS) of RS using synthetic polymer stabilizer (SPS) and natural polymer stabilizer (NPS), and to determine the optimum application concentration and mixing ratio of the PAM and Guar gum mixture. Results illustrated that PAM apparently outperform Guar gum in stabilizing sand particles. The mixture of PAM and Guar gum is more effective than individual use. The optimum polymer concentration and the mixing ratio are 0.94 wt.% and 0.6 (PAM: total (PAM + Guar gum)), respectively. A rigorous regression model was developed to predict the UCS value based on application concentration and mixing ratio for the purpose of cost and time efficiency.